2023
DOI: 10.5435/jaaos-d-22-00105
|View full text |Cite
|
Sign up to set email alerts
|

Ganglions in the Hand and Wrist: Advances in 2 Decades

Abstract: Ganglion cysts represent the most common soft-tissue mass in the hand and wrist. Ganglion cysts are most commonly encountered at the dorsal or volar aspects of the wrist, although cysts may arise from the flexor tendon sheath, interphalangeal joint, and extensor tendons. Intraosseous and intraneural ganglion cysts have also been described. Diagnosis of ganglion cysts relies primarily on history and physical examination. Transillumination and aspiration of masses may be useful adjuncts to diagnosis. Imaging suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(37 citation statements)
references
References 56 publications
(80 reference statements)
0
37
0
Order By: Relevance
“…A ganglion cyst is the most common benign fluid-filled tumor of the wrist (can also occur in the knee and foot) and accounts for up to 70% of the tumors in the wrist and hand 1 . Women are affected at a rate 3 times that of men and occur more in the second to fourth decades of life [2][3][4] . Ganglion cysts are frequently found in the dorsal wrist (70%), volar (palmar) wrist (20%), volar reticular cyst (10%), dorsal aspect of the distal interphalangeal (DIP) joint (mucous cyst), flexor tendon sheath at the level of the metacarpophalangeal (MCP) joint, intraosseous (within bone), and intraneural ganglions [1][2][3][4][5] .…”
Section: Ganglion Cystmentioning
confidence: 99%
See 4 more Smart Citations
“…A ganglion cyst is the most common benign fluid-filled tumor of the wrist (can also occur in the knee and foot) and accounts for up to 70% of the tumors in the wrist and hand 1 . Women are affected at a rate 3 times that of men and occur more in the second to fourth decades of life [2][3][4] . Ganglion cysts are frequently found in the dorsal wrist (70%), volar (palmar) wrist (20%), volar reticular cyst (10%), dorsal aspect of the distal interphalangeal (DIP) joint (mucous cyst), flexor tendon sheath at the level of the metacarpophalangeal (MCP) joint, intraosseous (within bone), and intraneural ganglions [1][2][3][4][5] .…”
Section: Ganglion Cystmentioning
confidence: 99%
“…However, Ledderhose proposed that mucoid degeneration was the origin of ganglion cyst formation due to repetitive connective tissue microtrauma with surrounding soft tissues that wall off mucin forming a cyst. 3,5 More recent research has shown that a fluid-filled stalk connects the cyst to adjacent periarticular structures. The lack of retrograde flow contributes to cyst formation and an increase in size over time.…”
Section: Ganglion Cystmentioning
confidence: 99%
See 3 more Smart Citations